Combating Information Attacks in the Age of the Internet: New Challenges for Cognitive Engineering. (December 2018) - Endsley, Mica R.
Objective: This article provides an overview of the characteristics of misinformation and information attack and their effects on the perceptions of the public, with the objective of outlining potential solutions and needed research for countering this growing problem. Background: Society is facing a significant challenge from the spread of misinformation through websites and social media that has driven a divergence in people's perceptions and understanding of basic facts associated with many issues relevant to public policy decisions, including the economy, taxation, and the deficit; climate change and the environment; and vaccinations and public health and safety. A number of factors are driving this fracture, including information presentation challenges that lead to poor information understanding, deliberate information attacks, social network propagation, poor assessments of information reliability, and cognitive biases that lead to a rejection of information that conflicts with preexisting beliefs. Results: A framework for understanding information attack is provided, including common sources, features, avenues, cognitive mechanisms, and major challenges in overcoming information attacks. Conclusion and Application: Potential solutions and research needs are presented for improving people's understanding of online information associated with a wide range of issues affecting public policy.